Online Career Job Dictionary as Media Improving Career Exploration of Junior High School Students - Mint Husen Raya Aditama (Teknodika, 2020)
Significantly the development of career exploration occurred at the age of adolescence (15-24 years). Career exploration aims to instill a positive attitude towards the workforce to students, the formation of early job choices, to improve knowledge about the external and the environment and the workforce, as well as how they can be congruent. This research considers students ' career exploration needs as a basis for determining the direction of student career choices in the future. The level of understanding of student career is based on deepening of the material ofathe dictionary of online career (kjko) measured using the instrument ces (career exploration survey).